2011
DOI: 10.1021/pr100918u
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Protein Interaction Network in Methicillin-Resistant Staphylococcus aureus

Abstract: Mortality attributable to infection with methicillin-resistant Staphylococcus aureus (MRSA) has now overtaken the death rate for AIDS in the United States, and advances in research are urgently needed to address this challenge. We report the results of the systematic identification of protein-protein interactions for the hospital-acquired strain MRSA-252. Using a high-throughput pull-down strategy combined with quantitative proteomics to distinguish specific from nonspecific interactors, we identified 13,219 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 62 publications
1
47
0
Order By: Relevance
“…24 This was based on the supposition that hub proteins are not only critical for bacterial survival but should be very sensitive to mutations 5 and targeting them should reduce the potential for development of resistance strains and species. In silico library screening, initially directed to putative binding sites unique to MRSA PK, combined with enzyme assays identified several active MRSA PK inhibitors including compound 1 6 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…24 This was based on the supposition that hub proteins are not only critical for bacterial survival but should be very sensitive to mutations 5 and targeting them should reduce the potential for development of resistance strains and species. In silico library screening, initially directed to putative binding sites unique to MRSA PK, combined with enzyme assays identified several active MRSA PK inhibitors including compound 1 6 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, given that hubs are generally essential for network integrity, they are expected to be less prone to genetic mutations and subsequent resistance emergence due to the network centrality-lethality rule (12). To this end, we recently mapped the architecture of a protein interaction network (PIN) between 608 proteins of S. aureus MRSA252 (7). As a result of this analysis, pyruvate kinase (PK), the product of a single-copy gene, was identified as a highly connected hub protein in MRSA.…”
mentioning
confidence: 99%
“…It has been observed that topological features like DC and BC have gained much importance in serving as attractive drug targets [36,44,45]. However, despite their potential to locate such targets, these measures lack in the specificity and/or selectivity along with the high risk of side effects.…”
Section: Topological Analyses To Identify An Important Proteinmentioning
confidence: 99%
“…These core proteins were found to present in many subnetworks [84]. Thus, the organism's interaction network can be used to predict the function of the unannotated proteins or to map protein complexes and pathways involved in virulence, providing the directions for uncovering new drug targets [44,84,87]. Network topology was exploited to identify essential genes/proteins, which are crucial for replication, growth and viability of an organism, in different human host have been studied [94][95][96].…”
Section: Analyses Of Pathogenic Pins: Intra-and Interspecies Scenariomentioning
confidence: 99%